Polychaeta collected during the research cruises TALUD aboard the R/V “El Puma” in the Mexican Pacific: Sabellidae and Serpulidae - Tovar-Hernández, María Ana; León-González, Jesús Angel De; Hendrickx, Michel E. (Zootaxa, 2025)
A total of 17 species of tubiculous worms (15 sabellids and 2 serpulids) were identified from deep-sea environment in the Gulf of California, off the west coast of the Baja California Peninsula, and off Guerrero, western Mexico. In addition, two sabellids were included from shallow waters for comparative purposes. Eleven sabellids are new to science: two in the genus Bispira, one each in the genera Chone, Claviramus, Euchone, and Jasmineira, two each in the genera Myxicola and Perkinsiana, and one in the genus Potamethus. Three taxa were identified at genus level (Branchiomma, Hydroides and Pseudopotamilla) and one as confer (Chone cf. mollis). Euchone cortezi Reish, 1968 is reinstated. Fabrisabella vasculosa Hartman, 1969 and Hyalopomatus biformis (Hartman, 1960) constitute new records in Mexico. Hydroides sp. (Serpulidae) is the first record of the genus in deep waters of the continental slope (2,077 m).